Are Altruists Environmentally Responsible and Materialists Environmentally Irresponsible? An Analysis on the Moderation of Social Desirability and Mediation of Environmental Awareness - Thiago Costa; Heidy Ramos; Leonardo Vils; Julio Cunha (BBR: Brazilian Business Review)
We investigated if altruism and materialism can explain attitudes related to the lower impact on the environment. This study aims to investigate the role of environmental awareness as a mediating variable between altruism and environmental responsibility, and if materialistic individuals can manifest environmental responsibility through social desirability. Also, we investigated the relations of altruism and materialism with environmental irresponsibility. Using the structural equations model, we analyzed the data from a survey with 339 individuals. The results conclude that altruism does not have a direct relationship with environmental irresponsibility, but has a relationship with environmental responsibility, not direct, but mediated by environmental awareness. Besides a direct relationship between materialism and environmental irresponsibility, we did not find a direct relationship with environmental responsibility, not even with the moderation of social desirability. This study shows values and attitudes that collaborate with pro-environmental behaviors, demonstrating the importance of environmental awareness for individuals to engage in actions favorable to sustainable consumption.